SAPI BETINA DALAM SURAH AL-BAQARAH (Kajian Semiotika) - Muhamad Dahyal Aqil (LUGATUNA: Jurnal Prodi PBA, 2022)
The purpose of this study of Semiotic against “Cow In Surah al-Baqarah”. This study is focused to the animal of a cow in the al-Baqarah, because it’s so unique in the Qur’an. The purpose of the study is to discuss a cow in the al-Baqarah through the semiotic approach. So, the authors chose the study of semiotic’s of a cow in the surah al-Baqarah as an object of study material and semiotic analysis of the animal in the Qur’an. To discuss these problems, researchers used by Roland Barthes semiotic approach. The data of this study were analyzed using semiotics techniques, in the form of Heuristic reading as a first-level semiotic analysis, and Hermeneutic reading as a second-level semiotic analysis. As for the “Cow in Surah al-Baqarah” who became the object of this study. The object in this study is the verses relating to the animals above. The results obtained from this review from the conclusion that; cows as God’s creatures, explained in the story of the Prophet Moses and the Children of Israel to look for him and slaughter him as an intermediary for miracles from God, because of the opposition and conflict that they had. Researches get four moral messages of cows in the surah al-Baqarah, which is about patience, obedience, firmness, and greatness of God.